The Impact of Augmented Reality-Based Platforms on Customer Behavioral Responses in Customer Travel - Jalalzadeh, Seyyed Reza; Haji Karimi Sari, Abbas Ali; shirani, Mahdiye (AI and Tech in Behavioral and Social Sciences, 2025)
With the increasing popularity of online shopping, the need for a method that can create a different and innovative perception of a brand in customers’ minds is of great importance. Augmented reality (AR) is a novel technology that can play a significant role in the field of online sales. To this end, customers of interior design products and furniture in Tehran were selected as the target population, and a quantitative approach and electronic questionnaire distribution were used to investigate the impact of AR-based platforms on customer behavioral responses in customer travel. The sample size of this study was 288 individuals determined using G*Power software. According to the findings of the article, augmented reality technology has a considerable influence on customers’ decisions. When AR-based platforms are used at any point during customer travel, due to the features of this technology, customers’ sense of immersion, enjoyment, and interest in the product increases, leading to increased trust in their choices, the perceived usefulness of the platform, and overall positive attitudes. Ultimately, this results in an increased intention to reuse the platform and purchase intention among customers. Therefore, it is recommended that managers of companies involved in the field of interior design products and furniture do not overlook the potential of this technology in their business development.